Crosstalk between dendritic cells and T lymphocytes during atherogenesis: Focus on antigen presentation and break of tolerance - Bellini, Rossella; Bonacina, Fabrizia; Norata, Giuseppe Danilo (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis is a chronic disease resulting from an impaired lipid and immune homeostasis, where the interaction between innate and adaptive immune cells leads to the promotion of atherosclerosis-associated immune-inflammatory response. Emerging evidence has suggested that this response presents similarities to the reactivity of effector immune cells toward self-epitopes, often as a consequence of a break of tolerance. In this context, dendritic cells, a heterogeneous population of antigen presenting cells, play a key role in instructing effector T cells to react against foreign antigens and T regulatory cells to maintain tolerance against self-antigens and/or to patrol for self-reactive effector T cells. Alterations in this delicate balance appears to contribute to atherogenesis. The aim of this review is to discuss different DC subsets, and their role in atherosclerosis as well as in T cell polarization. Moreover, we will discuss how loss of T cell tolerogenic phenotype participates to the immune-inflammatory response associated to atherosclerosis and how a better understanding of these mechanisms might result in designing immunomodulatory therapies targeting DC-T cell crosstalk for the treatment of atherosclerosis-related inflammation.